Characteristics of the Coal Fines Produced from Low-Rank Coal Reservoirs and Their Wettability and Settleability in the Binchang Area, South Ordos Basin, China. (5th April 2021) - Chen, Yue; Ma, Zhuoyuan; Ma, Dongmin; Zhang, Zhicang; Li, Weibo; Yang, Fu; Ji, Yusong; Peng, Tao
Abstract : By using proximate analysis, X-ray diffraction mineral analysis, scanning electron microscope, contact angle measurement, and settlement simulation experiment, the coal fines produced from the coalbed methane wells of Binchang area were used to study the characteristics including particle size distribution, composition, morphology, wettability, and settleability. The results show that the particle size of coal fines produced from coalbed methane wells are mainly >20 mesh, ranging of 1-400 μ m, and the particle size distribution curve is mainly dominated by the main-secondary bimodal type, with the main peak of 30-300 μ m. The particle size from large to small is drill cutting coal fines, flowback coal fines, bailing coal fines, and pipeline filter coal fines. In terms of ash content, coal fines are higher than coal seam, and drilling cuttings are higher than bailing coal fines, while the fixed carbon content of the former is lower than that of the latter. The minerals of coal fines are mainly kaolinite, illite, quartz, and other 6 minerals, and the mineral types of drilling coal fines are the most abundant, while the bailing coal fines only contain illite and quartz. The roundness of coal fine particles ranges from excellent to poor in the order of bailing coal fines, pipeline filter coal fines, flowback coal fines, and drilling cuttings. However, the sorting of drilling cuttings is excellent, and the particle edges are straight, neat, and smooth, while the sorting of bailing coal fines is poor, and the particle edges are curved, uneven, and rough. The contact angles of coal fines are 40.25°-69.5°, indicating hydrophilous. The wettability of bailing coal fines is better than that of drilling cuttings. The particle size has a negative correlation with the wettability effect. The more obvious the modification effect of positive wetting agent is, the worse the modification effect of negative wetting agent is. The modification of surfactant has nothing to do with the particle size of the coal fines, but is closely related to organic components and minerals. The larger the coal particle size, the higher the settling rate, and the higher the ash content and the lower the fixed carbon content, the faster the settling rate. With the dividing point 150 mesh, the settling rate of large particles is mainly affected by particle size, while that of small particles is affected by the composition.